The excess of Kahoot for pre-service teacher as an evaluation tool - Nurma Angkotasan; Wilda Syam Tonra; Suryani Taib (International Journal on Teaching and Learning Mathematics, 2019)
Technology-based instrument is one of the main factors in improving the quality of learning in the classroom. The purpose of the study was to see pre-service teacher' response using  Kahoot as evaluation tool. This study was carried out on third year students in  UniversitasKhairun. The study employed a questionnaire that consists of 15 items about the excess of Kahoot. A total of 23 subjects participated in this study. The students highly perceived Kahoot as a game that can increase self-confidence, a fun game, interesting game, and the most useful tools to be used later when the students become teacher